The Effectiveness of Health-Community-Based Waste Management in Yogyakarta - Mulasari, Surahma Asti; Husodo, Adi Heru; Muhadjir, Noeng (Universitas Negeri Semarang, 2016)
The people’s understanding of waste affects their attitudes and modes in waste management. The attitudes towards health-community-based waste management has their positive impact i.e. improving environmental and community health and in the end promoting community’s economy. This research aimed at understanding the effectiveness of health-community-based waste management in Yogyakarta indicated by the residents’ knowledge of waste, attitude, behavior, and the existence of desease vector and economical condition. This was a social action research, which applied a quantitative method. The research was conducted through implementing waste management based on community health perception. The data-collecting technique involved observation participant technique. There was a significant difference between people’s knowledge on waste management before and after waste management counselling with p value 0.000 < 0.05. There was a significant difference between the people’s attitude before and after waste management counselling with p value 0.021 < 0.05. There was a significant difference between the people’s behavior before and after waste management counselling with 0.033 < 0.05. There was a significant difference between the density of fly population before and after waste management counselling with p value 0.013 < 0.05. The average of 30 participants’ income earned from garbage is IDR 55.952.83 quarterly or IDR 18.650.61 (IDR 13.450.00 = 1 US). The conclusion is knowledge, attitude, behavior indicators and vector density improved after the training of health-communicty based waste management.